Kreativitas Guru Al Qur’an Hadist dalam Mendesain Model Pembelajaran Berbasis Literasi Digital dalam Masa Pandemi - Siti Aniqoh; Muhammad Anas Ma`arif; Ari Kartiko (Center of Education Journal (CEJou), 2021)
The purpose of this article is to analyze the creativityof Al Qur'an Hadith teachers in designing digital literacy-based learning models during the pandemic at Madrasah Aliyah Al Hidayah Jenu Tuban. This study uses a qualitative method with a case study approach. Data collection techniques using interviews, observation, and documentation. The results showed that: 1) The creativity of Al Qur'an Hadith teachers in designing digital literacy-based learning models during the pandemic at Madrasah Aliyah Al Hidayah Jenu Tuban was good, this was shown through the teacher's ability to create new ideas to design creative learning models. , a form of teacher creativity in utilizing digital media into a learning process that is quite interesting so that the learning process carried out can run effectively, interestingly, and fun. 2) The challenges of Al Qur'an Hadith teachers in designing digital literacy-based learning models during a pandemic, namely: (a) developing intellectuality, (b) being adaptive in all changes, (c) being up-to-date in the fields of education and technology, (d) consistency in carrying out tasks.